Analisis Pengaruh Cover Mika Bening pada Panel Surya Monokristal 50WP terhadap Pengisian Baterai Skuter Listrik (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The advancement of automotive technology has accelerated the adoption of renewable‑energy‑based electric vehicles, including the integration of solar panels on electric scooters. Indonesia’s tropical climate provides abundant solar energy potential; however, the limited surface area of scooters often restricts panel placement to the footrest section. This study aims to evaluate the impact of using a 10 mm clear acrylic cover on the performance of a 50 Wp monocrystalline solar panel in an electric scooter battery‑charging system. An experimental method was employed by comparing the panel’s performance under two conditions: without a cover and with the acrylic cover installed. Key parameters observed included voltage, current, and charging power, recorded using a data logger. Tests were conducted for 30 minutes under varying solar radiation intensities. The results indicate that the acrylic cover reduces the panel’s output power, from 55 W to 45 W at a solar radiation intensity of approximately 1100 W/m². These findings suggest that the use of an acrylic cover must be carefully considered to maintain optimal charging system performance.